The ferroxidases are critical for Fe(II) oxidation in xylem to ensure a healthy Fe allocation in Arabidopsis thaliana - Zhu, Qing-Yang; Wang, Yun; Liu, Xing-Xing; Ye, Jia-Yuan; Zhou, Miao; Jing, Xiang-Ting; Du, Wen-Xin; Hu, Wei-Jie; He, Chao; Zhu, Ya-Xin; Jin, Chong-Wei (Frontiers in Plant Science, 2022)
The long-distance transport of iron (Fe) in xylem is critical for maintaining systematic Fe homeostasis in plants. The loading form of Fe(II) into the xylem and the long-distance translocation form of Fe(III)-citrate have been identified, but how Fe(II) is oxidized to Fe(III) in the xylem remains unknown. Here, we showed that the cell wall-resided ferroxidases LPR1 and LPR2 (LPRs) were both specifically expressed in the vascular tissues of Arabidopsis thaliana, while disruption both of them increased Fe(II) in the xylem sap and caused excessive Fe deposition in the xylem vessel wall under Fe-sufficient conditions. And as a result, a large amount of Fe accumulated in both roots and shoots, hindering plant growth. Moreover, under low-Fe conditions, the LPRs were preferentially induced in old leaves, but loss of LPRs increased Fe deposition in the vasculature of older leaves and impeded Fe allocation to younger leaves. Therefore, disruption of both LPRs resulted in severer chlorosis in young leaves in response to Fe-deficiency. Taken together, the oxidation of Fe(II) to Fe(III) by LPRs in the cell wall of vasculature plays an important role in xylem Fe allocation, ensuring healthy Fe homeostasis for normal plant growth.